Pelayanan Pihak Rumah Sakit Swasta Terhadap Pasien Miskin di Kota Lhokseumawe - Cut Muftia Keumala; Zanzibar Zanzibar (Sekolah Tinggi Ilmu Administrasi Nasional, 2020)
The hospital as a health service facility has a very strategic role in an effort to accelerate the improvement of the health status of the Indonesian citizens - both public and private hospitals. This is because hospitals have the capacity of affording quality health services that are affordable to the poor community. Based on the research results, it shows that the health services provided by the Bunda Lhokseumawe Hospital have been carried out optimally according to the applicable procedures. Patient satisfaction with the health services. There are those who give satisfying responses to a friendly doctor's attitude and there are also the patient's responses that are not satisfactory. The lack of ability of IT operators to computer applications is a very fatal obstacle in online administration services. To overcome this predicament, intensive socialization and training are required for the IT operators so that they will be able to overcome various obstacles in the event of technical errors during data entry. Another obstacle to health services carried out by the Bunda Lhokseumawe Hospital for patients is the lack of specialist doctors. To overwhelm this matter, the management must recruit more specialist doctors to the hospital.